Vaccination of cattle with a DNA plasmid encoding the bovine viral diarrhoea virus major glycoprotein E2 - Harpin, Serge; Hurley, David J.; Mbikay, Majambu; Talbot, Brian; Elazhary, Youssef (Journal of General Virology, 1999)
Bovine viral diarrhoea virus (BVDV) is an economically important pathogen of cattle that is ubiquitously distributed worldwide. In this study, cattle were immunized by intramuscular injections with plasmid DNA expressing the BVDV type 1 major glycoprotein E2. Animals either received injections of naked DNA (N-DNA) or DNA in cationic liposomes (L-DNA). Both DNA preparations induced virus-specific neutralizing antibodies in vaccinates, although the response was much lower in N-DNA-immunized animals. N-DNA-vaccinated animals also showed virus-specific lymphocyte proliferation responses to type 1, live BVDV in vitro, whereas L-DNA vaccination induced no such responses. After 16 weeks, DNA-vaccinated and mock-vaccinated animals were challenged with a USDA-certified BVDV type 1 strain. Four significant observations were made: (1) N-DNA-vaccinated calves showed limited protection from virus challenge, (2) L-DNA-vaccinated animals did not show any signs of protection, (3) the challenge induced strong memory responses in the production of serum neutralizing antibodies to both genotypes (type 1 and 2 of BVDV), and (4) the challenge induced a mucosal memory response in nasal secretions of both L- and N-DNA-vaccinated animals.